Analisis kebijakan penyederhanaan RPP: Surat edaran menteri pendidikan dan kebudayaan nomor 14 tahun 2019 - I Kadek Yogi Mayudana; I Komang Sukendra (Indonesian Journal of Educational Development, 2020)
Education in the era of the industrial revolution 4.0 is directed at developing 21st century competencies, which consist of three main components namely thinking, acting and living in the world. The thinking component includes critical thinking, creative thinking, and problem solving skills. So that goals can be achieved, good planning is needed, teachers will be easier to carry out learning and students will be more helped and easier to learn. According to the Minister of Education and Culture the important thing in a learning implementation plan is not about writing, but about the teacher's reflection process towards learning that occurs. The main task of a teacher is to educate, with the simplification of this lesson plan the teacher will return to the main points and functions because there is no need to take care of the lesson sheet in pieces. School accreditation instruments also need to be considered so that there is no overlap between school accreditation and circular letter 14 of 2019 Simplifying the Learning Implementation Plan. Pendidikan pada era revolusi industri 4.0 diarahkan untuk pengembangan kompetensi abad 21, yang terdiri dari tiga komponen utama yaitu berpikir, bertindak dan hidup di dunia. Komponen berpikir meliputi berpikir kritis, berpikir kreatif, dan kemampuan pemecahan masalah. Agar tujuan itu dapat tercapai, maka diperlukan perencanaan yang baik, guru akan lebih mudah dalam melaksanakan pembelajaran dan siswa akan lebih terbantu dan mudah dalam belajar. Menurut Mendikbud hal yang penting dalam sebuah rencana pelaksanaan pembelajaran bukan tentang penulisannya, melainkan tentang proses refleksi guru terhadap pembelajaran yang terjadi. Tugas utama seorang guru adalah mendidik, dengan penyederhanaan RPP ini guru akan kembali kepada pokok dan fungsi utamanya karena tidak perlu lagi mengurusi RPP yang berlembar-lembar. Instrumen akreditasi sekolah juga perlu diperhatikan agar tidak tumpang tindih antara akreditasi sekolah dan surat edaran Menteri Pendidikan dan Kebudayaan Nomor 14 Tahun 2019 Tentang Penyederhanaan Rencana Pelaksanaan Pembelajaran (RPP).